2003
DOI: 10.1097/01.ju.0000081052.51707.cf
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic and Peripheral Blood Selenium Levels After Oral Supplementation

Abstract: Oral selenium supplementation increases prostatic and peripheral blood levels in men in a nonselenium deficient population. Blood and prostate levels correlated poorly, suggesting that peripheral blood measurements are a poor indicator of prostatic selenium content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…An intriguing previous finding in 25 prostate cancer patients who had radical prostatectomies (12) indicated significantly higher concentrations of selenium in the peripheral zone, in which prostate cancer generally develops, than in the transitional zone; this finding, however, did not involve supplementation. There has been only one previous randomized study of selenium supplementation examining levels in the human prostate, which examined only (and found increased selenium in) the transitional zone (11). Our randomized, controlled study found that selenium supplementation resulted in increased selenium levels in the peripheral zone, in which prostate cancer develops most frequently (40), and that selenium accumulated selectively in the prostate instead of the SV.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…An intriguing previous finding in 25 prostate cancer patients who had radical prostatectomies (12) indicated significantly higher concentrations of selenium in the peripheral zone, in which prostate cancer generally develops, than in the transitional zone; this finding, however, did not involve supplementation. There has been only one previous randomized study of selenium supplementation examining levels in the human prostate, which examined only (and found increased selenium in) the transitional zone (11). Our randomized, controlled study found that selenium supplementation resulted in increased selenium levels in the peripheral zone, in which prostate cancer develops most frequently (40), and that selenium accumulated selectively in the prostate instead of the SV.…”
Section: Discussionmentioning
confidence: 63%
“…The previous evaluations of selenium in human prostate (10 -13) and other tissues (14) lacked controls for differentiating between the effects of dietary versus supplemental selenium, or analyzed very few prostate tissue samples (15). We are aware of only one prior randomized study of supplemental selenium that examined selenium levels in prostate tissue (11). The limitations of the study included the availability of only transitional zone prostate tissue (from patients undergoing transurethral resection for benign prostatic hypertrophy), no sampling of other tissues to assess selectivity of selenium uptake in prostate tissue, and lack of control for chronic (dietary) selenium intake.…”
mentioning
confidence: 99%
“…Beguin et al [25,26] reported that tumors could, depending on "tumor activity," retain Se and serum Se level in patients with acute nonlymphocytic leukemia. Gianduzzo et al [27] showed that men who received daily oral Se supplementation for 30 d have statistically significant higher concentrations of Se in the prostate than those receiving a placebo, although the Se levels in the prostate and peripheral blood were poorly correlated. In this study, 7 d treatment with escalating doses of MSC was associated with sequential increases of intratumoral Se concentrations in both FaDu and A253 tumors (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This might be taken as an indirect indication in favor of selenium supplementation for the purpose of PC prevention. Two studies showed that oral administration of selenium, in comparison to controls, lead to a significant increase in the PTSL [28,29], but not in the seminal vesicles [29].…”
Section: Discussionmentioning
confidence: 99%